MODELING THE PURCHASE DECISION AND CUSTOMER LOYALTY MECHANISM USING AGENT-BASED SIMULATION - Mahdi Tomiputra, Syafiq
Purpose: It has been proven time and time again that gaining new customers costs five to 25 times more than retaining existing ones. The people who have bought from a company three times are 54% more likely to buy from the same company for their next purchase. And that engaged customers spend 16% more than the average customers. All of this leads up to the point that catering to existing customers increases profitability. Thus, proving the need for customer loyalty. This research has the objective of identifying the mechanism behind a customer’s purchase decision and the buildup of customer loyalty through repeat purchases. The second objective of the research is to identify the timing to launch a loyalty program in relation to the market segments proportion. Methodology: Because the target system is considered a complex system, agent-based modeling is used to capture the dynamics of human interaction. Literature review and interviews are used to set basic assumptions used in the model. The model created will be a generic model, one that is not tailored to capture a specific industry. Internal validation test is used to validate the model, and corner testing the market segment proportions to determine how the timing to launch a loyalty program will differ depending on the market segment proportions. Findings: The findings of this research dictates that a person will decide to purchase if it is sufficiently affected by recommendations, advertisements, and the benefits of a loyalty program. The research shows that there is a significant difference in optimal time to post a loyalty program depending on the proportion of the market segments. The emerging property of the simulation is that the number of purchases increase drastically after the company launches a loyalty program.